The Use of the Nematode Caenorhabditis elegans to Evaluate the Adverse Effects of Epoxiconazole Exposure on Spermatogenesis - Li, Yunhui (Int J Environ Res Public Health, 2016)
There is increasing evidence that epoxiconazole exposure can affect reproductive function, but few studies have investigated adverse effects on spermatogenesis. The nematode Caenorhabditis elegans (C. elegans) was used in our study to assess effects of epoxiconazole on spermatogenesis in male nematodes after 48 h of exposure to concentrations of 0.1, 1.0, or 10.0 μg/L. The results demonstrated that epoxiconazole exposure affected spermatogenesis, decreasing the number of total germ cells, mitotic cells, meiotic cells and spermatids, spermatid diameter, and cross-sectional area, and inducing mitotic germ cell proliferation arrest, premature entry into meiosis, and sperm activation inhibition; however, sperm transfer showed no abnormal changes. In addition, the results showed that epoxiconazole activated the transforming growth factor-β (TGFβ) signaling pathway and increased the expression levels of gene daf-1, daf-3, daf-4, daf-5 and daf-7 in nematodes. We therefore propose that epoxiconazole acts by activating the TGFβ signaling pathway, leading to the impairment of spermatogenesis and the consequent decline in male fertility.